2017
DOI: 10.1111/chd.12456
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia in infants with single ventricle anatomy following stage 1 palliation: Physiologic correlates and response to treatment

Abstract: Background Deficits in swallowing physiology are a leading morbidity for infants with functional single ventricles and systemic outflow tract obstruction following stage 1 palliation. Despite the high prevalence of this condition, the underlying deficits that cause this post-operative impairment remain poorly understood. Objective Identify the physiologic correlates of dysphagia in infants with functional single ventricles and systemic outflow tract obstruction following stage 1 palliative surgery. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 42 publications
(91 reference statements)
2
37
0
2
Order By: Relevance
“…Systematic enteral feeding algorithms and home nutritional monitoring programs have F I G U R E 1 Flow chart of study population derived from NPC-QIC registry and feeding methods at discharge following S2P. 7,16 To our knowledge, this is the first multicenter study to examine feeding method at S2P discharge for this high-risk population, and define patient characteristics associated with feeding method during S2P hospitalization and discharge. 5,[13][14][15] Evidence-based protocols that encompass all phases of palliative surgery to guide decision making for introduction and advancement of oral feeding are not available.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Systematic enteral feeding algorithms and home nutritional monitoring programs have F I G U R E 1 Flow chart of study population derived from NPC-QIC registry and feeding methods at discharge following S2P. 7,16 To our knowledge, this is the first multicenter study to examine feeding method at S2P discharge for this high-risk population, and define patient characteristics associated with feeding method during S2P hospitalization and discharge. 5,[13][14][15] Evidence-based protocols that encompass all phases of palliative surgery to guide decision making for introduction and advancement of oral feeding are not available.…”
Section: Discussionmentioning
confidence: 99%
“…23 Of note, many centers try to promptly extubate following 4-5 days or 1 week; therefore, the multicenter data definition of prolonged intubation >14 days was a limitation in our study. 7,24 Additional studies are needed to elucidate long-term implications for RLN injury and recovery, and swallowing outcomes. Therefore, although uncommon, prolonged intubation may be a marker of greater complications during the stage 2 admission (see Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oropharyngeal dysphagia is a known complication for infants with congenital heart disease (CHD), though estimates of both incidence and severity of swallowing dysfunction are variable . Many infants born with CHD, including those with hypoplastic left heart syndrome (HLHS), require invasive cardiothoracic surgery within the first days of life.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the data that exists regarding swallowing in infants with CHD is reported following the Norwood procedure. Only two studies specifically examine feeding and swallowing outcomes following the hybrid procedure . However, both of these studies were limited because rates of swallowing dysfunction were reported only among patients that were already suspected of having dysphagia, increasing the likelihood of subsequently identifying swallowing impairments during instrumental assessment.…”
Section: Introductionmentioning
confidence: 99%